Relationship between the Superior Attachment of the Uncinate Process and Pneumatization of the Middle Turbinate—A Radiological Study - Christian Calvo-Henriquez; Miguel Mayo-Yañez; Carlos M. Chiesa-Estomba; Gabriel Martinez-Capoccioni; Carlos Martin-Martin (Surgeries, 2022)
Objective: the superior attachment of the uncinate process (SAUP) is highly variable. Lateral types of SAUP are associated with frontal rhinosinusitis. SAUP in the middle turbinate is more common when the middle turbinate is aerated. We aim to refine these findings by studying the relationship between the SAUP type and the different subtypes of pneumatization of the middle turbinate. Methods: 200 CT sinonasal scans were analyzed by an otolaryngologist and a radiologist. All CT scans were analyzed to study the type of the middle turbinate concha bullosa and lamellar cell and the type of SAUP. Results: 379 sides were analyzed. The prevalence of the various types of SAUP were: Type I: 43.80%, Type II: 22.16%, Type III: 16.36%, Type IV: 3.69%, Type V: 9.76%, and Type VI: 4.22%. When studying the pneumatization of the middle turbinate and the SAUP types, we only found a statistically significant association between the lateral attachment of the uncinate process and the presence of a lamellar cell (p = 0.029). Conclusion: lateral types of SAUP are more likely in the presence of a lamellar cell. This finding, therefore, renders checking for lateral SAUP types in the presence of a lamellar cell even more relevant than when studying the pre-surgical CT scan. In those cases, it is advisable to perform a careful and complete uncinectomy.